Overspreading of toponyms in dependence on economic development in the example of Mountain Zlatibor - Vemić Mirčeta (Zbornik Radova: Geografski institut "Jovan Cvijić", 2008)
Toponyms are proper geographic names of longer historic-geographic continuation. Local population inherits them by generation, remember them and inform both descendants and population of their spatial encirclement. In science toponyms denoting concrete geographic objects are recorded and written on maps with certain spatial borders representing thus a very stable element in studying geographic area. Changes of toponyms occur in longer time, i.e. civilization epochs, and very rarely in shorter time periods, these are usually the cases of sudden change of population or changes of political-historical circumstances of a territory. However, as linked to human conscience, toponyms often get different internal spatial meanings as well as different territorial belonging, where, in dependence on causes, they get narrower or overspread as in the case of Zlatibor toponyms. Total economic development of Zlatibor in the last more than a hundred years has caused this toponym spatially spread and got new forms. It appeared as oronym (name of relief object) and it has kept the same meaning up today, although in one period it was recorded as horonym (regional name) on maps. In the last decade it also appeared as oikonym (name of settlement)-Zlatibor, the name for ex settlement of Kraljeva Voda, later Partizanske Vode, joined with Palisad, but also as the name for wider spatial-administrative region-Zlatibor Region. At the same time, by spreading Zlatibor toponym, the toponyms of Cigota, Tornik and Murtenica are narrowed territorially, while with similar continuation of economic development it may be expected that Zlatibor toponym will overspread on the territory of Tara and Zlatar Mountains in the future, while these ones will reduce on names of their parts-peaks.